제설 기능을 갖는 LED 신호등 렌즈 개발 - 이동은; 설동열; Lee, Dongeun; Seol, Dongyoul ((사)디지털산업정보학회 논문지, 13(4), 2017)
It is necessary to develop an LED traffic light lens having a snow removal function capable of clearly providing a traffic signal to the driver even when a traffic light is blurred due to heavy snow and wind in the winter season. This study is focused on the research and development of the traffic light lens in the process of developing the LED traffic light with the snow removal function. In the developed traffic light lens, instead of attaching the film heater, the coated nichrome wire was wound into a coil shape and inserted directly into the groove in the lens. The developed heater system facilitates the insertion of the heating wire with high elasticity into a curved lens and can provide a sufficient heat without deformation of the PC lens. The proposed traffic lights were tested in various external environments and the test results showed that complete snow removal is possible without tunnel effect.